Up-regulation of silent information regulator 2 (Sir2) is associated with amphotericin B resistance in clinical isolates of Leishmania donovani. (8th February 2015) - Purkait, Bidyut; Singh, Ruby; Wasnik, Kirti; Das, Sushmita; Kumar, Ashish; Paine, Mark; Dikhit, Manas; Singh, Dharmendra; Sardar, Abul H.; Ghosh, Ayan K.; Das, Pradeep
Abstract: Objective: Silent information regulator 2 (Sir2) is involved in parasite survival and apoptosis. Here, we aimed to explore the involvement of Sir2 in amphotericin B (AmB) resistance mechanism in Leishmania donovani . Methods: The expression levels of Sir2, MDR1 and NAD + biosynthetic pathway enzymes in AmB-resistant and -susceptible parasites were measured and total intracellular NAD + /NADH ratios were compared. Overexpression and knockout constructs of Sir2 were transfected in AmB-resistant and -susceptible parasites. Both resistant and susceptible parasites were inhibited with sirtinol for 4 h. The deacetylase activity of Sir2, the expression level of MDR1, the rate of AmB efflux, concentrations of reactive oxygen species (ROS) and levels of apoptosis were examined in WT, inhibited and transfected parasites, and the AmB susceptibility of the respective parasites was measured by determining the LD50 of AmB. Results: Levels of mRNA, protein and NAD + -dependent deacetylase activity of Sir2 were elevated in resistant versus susceptible parasites. Inhibition and/or deletion of Sir2 allele showed a decreased mRNA level of MDR1, lower drug efflux, increased ROS concentration, apoptosis-like phenomenon and decreased LD50 of AmB in resistant parasites. In contrast, Sir2 overexpression in susceptible parasites reversed drug susceptibility producing a resistant phenotype. This was associated with increased LD50 of AmB along with increased expression levels of MDR1, drug efflux and reduced concentrations of ROS, corresponding to decreased apoptosis of resistant to WT sensitive. Conclusions: Sir2 plays a critical role in AmB resistance by regulating MDR1, ROS concentration and apoptosis-like phenomena and may be a new resistance marker for visceral leishmaniasis.